2007
DOI: 10.1016/j.ccr.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Lung Cancer-Derived EGFR Mutants and Inhibitor Complexes: Mechanism of Activation and Insights into Differential Inhibitor Sensitivity

Abstract: Mutations in the EGFR kinase are a cause of non-small-cell lung cancer. To understand their mechanism of activation and effects on drug binding, we studied the kinetics of the L858R and G719S mutants and determined their crystal structures with inhibitors including gefitinib, AEE788, and a staurosporine. We find that the mutations activate the kinase by disrupting autoinhibitory interactions, and that they accelerate catalysis as much as 50-fold in vitro. Structures of inhibitors in complex with both wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
980
3
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 970 publications
(1,028 citation statements)
references
References 49 publications
32
980
3
13
Order By: Relevance
“…However, the combined mutant E709A +G719S was not investigated. In another study on in vitro kinase assay, the catalytic activity of G719S mutant was found to be 10-fold more active than WT EGFR (29). As amino acid glycine at position 719 is part of the highly conserved glycine-rich GXGXΦG motif (719GSGAFG724) present in the ATP-binding loop of protein kinases, it is suggested that it plays a crucial role in WT EGFR function (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the combined mutant E709A +G719S was not investigated. In another study on in vitro kinase assay, the catalytic activity of G719S mutant was found to be 10-fold more active than WT EGFR (29). As amino acid glycine at position 719 is part of the highly conserved glycine-rich GXGXΦG motif (719GSGAFG724) present in the ATP-binding loop of protein kinases, it is suggested that it plays a crucial role in WT EGFR function (30).…”
Section: Discussionmentioning
confidence: 99%
“…The kinase domain of EGFR generally exists in an auto-inhibited inactive conformation that adopts an active conformation by asymmetric contacts made during receptor dimerization [36]. EGFR kinase domain mutations in lung cancers destabilize the inactive conformation thereby favoring the active state [175]. Erlotinib and gefitinib bind the active conformation of the kinase domain and are effective in suppressing the activity of wild-type and certain mutant EGFRs [173,175].…”
Section: Targeted Therapymentioning
confidence: 99%
“…EGFR kinase domain mutations in lung cancers destabilize the inactive conformation thereby favoring the active state [175]. Erlotinib and gefitinib bind the active conformation of the kinase domain and are effective in suppressing the activity of wild-type and certain mutant EGFRs [173,175]. The binding characteristics of each TKI appear to vary with the specific EGFR mutation and in the future the choice of TKI may be tailored to the unique molecular features of individual tumors.…”
Section: Targeted Therapymentioning
confidence: 99%
“…28 The EGFR-TKD is likely to be the major site for TKI-resistance related mechanism to operate, because not only T790M mutation lies within this region, but in fact gefitinib and erlotinib, both EGFR specific TKIs used in this study, bind to the TKD on EGFR. 36,37 Gefitinib and erlotinib both exhibit much higher affinity to the active conformation of the EGFR-TKD over the inactive form. We propose that T790M mutation causes the EGFR-TKD to assume an intermediate conformation that favors the kinase activity but reduces affinity to the TKIs, giving the NSCLC cells resistance to the treatment.…”
Section: Discussionmentioning
confidence: 99%